The role of the TNF receptors and apoptosis inducing ligands in tumor growth - O. H. Minchenko1; D. O. Tsymbal1; D. O. Minchenko1,2; О. O. Ratushna1 (The Ukrainian Biochemical Journal, 2016)
Tumor necrosis factor (TNF) superfamily receptors and TNF apoptosis inducing ligands play an important role in the realization of TNF function and control tumor growth. The TNF-related pathways are controlled by endoplasmic reticulum stress signaling, which has a crucial role in the control of cell proliferation and tumor growth. Furthermore, the inhibition of IRE1 (inositol requiring enzyme-1), which is a central mediator of endoplasmic reticulum stress sand mainly responsible for cell proliferation and apoptosis, leads to suppression of tumor growth through specific changes in the expression of genes encoding transcription factors, tumor suppressors, angiogenesis and apoptosis related proteins, including TNF superfamily receptors and TNF apoptosis inducing ligands. Therefore, changes in the expression level of TNF-related genes encoding TNF superfamily receptors and apoptosis inducing ligands possibly reflect metabolic reprogramming of cancer cells upon inhibition of IRE1-mediated endoplasmic reticulum stress signaling and correlate with suppression of glioma cell proliferation.